First record of the presence of the spittlebug Aeneolamia reducta (Lallemand, 1924) (Hemiptera: Cercopidae) in Valle del Cauca (Colombia) - CGIAR Research Program on Livestock (2020)
First record of Aeneolamia reducta (Lallemand, 1924) (Hemiptera: Cercopidae) in Valle del Cauca (Colombia), presenting a potential risk to sugarcane cultivation. Previously this species was reported in livestock production areas of the Caribbean coast, the Eastern plains and the Magdalena River valley in different species of cultivated pastures.